2003
DOI: 10.1210/jc.2003-030377
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Hormone Causes Vasodilation in Human Skin via Mast Cell-Dependent Pathways

Abstract: CRH plays a central role as a mediator of the hypothalamic-pituitary-adrenal axis and stress response and is a potent vasodilator. Previously, we have shown that CRH causes a gender-specific vasodilation in human skin, although the mechanism by which CRH operates is unclear. CRH causes mast cell degranulation in rat skin. As such, histamine and other mast cell-derived factors may be indirectly responsible for the vasodilatory effects of CRH, although CRH is also known to act directly on the vasculature. CRH-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 43 publications
1
54
0
8
Order By: Relevance
“…CRF and its related peptides reach the inflammation site either through sensory nerve terminals or via production by local epithelium and/or by the inflammatory cells themselves. A well-established target of CRF and UCN is the mast cell (12)(13)(14)(15)(16)(17). We have previously shown that CRF also affects monocytes/macrophages by augmenting LPS-induced cytokine production (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRF and its related peptides reach the inflammation site either through sensory nerve terminals or via production by local epithelium and/or by the inflammatory cells themselves. A well-established target of CRF and UCN is the mast cell (12)(13)(14)(15)(16)(17). We have previously shown that CRF also affects monocytes/macrophages by augmenting LPS-induced cytokine production (11).…”
Section: Discussionmentioning
confidence: 99%
“…CRF acts as an ad hoc proinflammatory factor because blockade of its effect by specific anti-CRF serum or CRF antagonists attenuates the inflammatory response in several models of inflammation including that of carrageenin, turpentine, and Gram-negative bacterial LPS-induced inflammation (9 -11). A well-defined immune target of CRF is the mast cell (12)(13)(14)(15)(16)(17). Indeed, mast cells express the CRF and the CRF-related protein urocortin (UCN) 1 and possess their specific binding sites (18).…”
mentioning
confidence: 99%
“…Iontophoretic coapplication of atropine (10 mM) caused a more profound reduction (27 Ϯ 8 PU; n ϭ 12; 26 Ϯ 4%; P Ͻ 0.01, paired Student's t-test). Thus our experimental procedures were working as would be predicted from previous studies (7,18), serving as positive controls for the following experiments. The response to menthol (Fig.…”
Section: Aorta Endotheliummentioning
confidence: 99%
“…CRH can also modify DNA synthesis in the dermal and epidermal compartments of cultured mouse skin depending on the phase of the hair growth cycle (24). These differential effects are apparently related to fluctuations in CRH-R1 and CRH-R2 expression during the hair growth cycle (20,24,65) Skin vasculature is a recognized target for CRH and urocortin peptides (6,(77)(78)(79), where, depending on the animal model used, CRH can induce local vascular dilatation (6,(77)(78)(79) and either inhibit or stimulate angiogenesis (80,81). Interestingly, both CRH and urocortin demonstrated anti-edema effects (82)(83)(84).…”
Section: Phenotypic Effects Of Crh and Urocortin In Cultured Skin Cellsmentioning
confidence: 99%
“…Interestingly, both CRH and urocortin demonstrated anti-edema effects (82)(83)(84). In the specific case of human skin, Clifton et al clearly have shown vasodilatory action of CRH, mediated by mechanisms that included both indirect effects, activation of mast cells or endothelial-dependent pathways, and a direct action on the blood vessel wall (77)(78)(79). These vascular effects of CRH appear to be dependent on the local level of estrogenization (77).…”
Section: Phenotypic Effects Of Crh and Urocortin In Cultured Skin Cellsmentioning
confidence: 99%